Influence of coagulation factors and tissue factor concentration on the thrombin generation test in plasma - Duchemin, Jérôme; Pan-Petesch, Brigitte; Arnaud, Bertrand; Blouch, Marie-Thérèse; Abgrall, Jean-François (Thrombosis and Haemostasis, 2008)
The thrombin generation test is used to study coagulation in patients with haemorrhagic diseases or with high thrombotic risk. To our knowledge, this is the first study investigating the relative influence of coagulation factors on thrombin generation in plasma. The aim was to investigate the influence of coagulant factors, anticoagulant factors, and tissue factor (TF) on three parameters: endogenous thrombin potential (ETP), peak thrombin concentration, and lag time for the appearance of thrombin. At a low TF concentration, all factors except factor XI influenced thrombin generation. At a high TF concentration, only the factors of the extrinsic pathway exerted an influence. ETP and peak thrombin were linearly correlated to factor II concentration. Factor V and factor VII effects increased hyperbolically with factor concentration. The influence of factor X on thrombin generation depended onTF concentration. In the absence of factorVIII and factor IX, ETP fell to 60–70% of the normal when peak thrombin fell to 25–30% of the normal. Fibrinogen concentration influenced ETP and peak thrombin and decreasing fibrinogen levels shortened the lag time. As expected, decreasing antithrombin concentration caused dramatic increases in thrombin generation. Protein S prolonged the lag time, especially at a low TF concentration. No effect of protein C was observed, likely due to the absence of thrombomodulin. The thrombin generation test was more sensitive to factor deficiencies at low than at high TF concentration. ETP was not the most critical parameter for studying coagulation factor deficiencies. Instead, peak thrombin was the most sensitive parameter.
Keywords: Anticoagulant factor; procoagulant factor; thrombin generation; tissue factor